2022
DOI: 10.1002/ajmg.a.62845
|View full text |Cite
|
Sign up to set email alerts
|

Genetic testing to gain diagnostic clarity in neurofibromatosis type 2 and schwannomatosis

Abstract: Neurofibromatosis type 2 (NF2) and schwannomatosis (SWN) have distinct genetic etiologies but overlapping phenotypes. Genetic testing may be required for accurate diagnosis, which is critical for determining prognosis, screening recommendations, and treatment options. Our study aimed to compare the efficacy of germline-only versus paired (germline and tumor) genetic testing for clarifying the diagnosis in patients with features of NF2 and SWN. We performed a retrospective chart review of patients referred for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…A diagnosis of NF2 can be made in case of bilateral vestibular schwannomas, presence of an identical NF2 pathogenic variant in at least two anatomically distinct NF-2-related tumors (e.g., schwannoma, ependymoma, meningioma) or when two major criteria or one major plus two minor criteria are met (major criteria: unilateral vestibular schwannoma, first-degree relative other than sibling with NF2, ≥2 meningiomas, NF2 pathogenic variant in unaffected tissue—if VAF < 50%, the diagnosis is mosaic NF2; minor criteria: more than one type of tumors, including ependymoma, meningioma, or schwannoma, juvenile subcapsula or cortical cataract, retinal hamartoma, epiretinal membrane in a person < 40 years) [ 74 ]. Genetic analysis uses next-generation sequencing plus multiplex ligation-dependent probe amplification for the detection from 1 exon to multiexon copy number changes and high resolution karyotyping for the identification of chromosomal rearrangements in the NF2 locus with a germline detection rate of 96% in the second generation of families with typical NF2 [ 75 ]. The germline detection rate decreases to 60% in mosaic NF2 [ 76 ].…”
Section: Genetic Tumor Syndromes Correlated With Cranial and Peripher...mentioning
confidence: 99%
“…A diagnosis of NF2 can be made in case of bilateral vestibular schwannomas, presence of an identical NF2 pathogenic variant in at least two anatomically distinct NF-2-related tumors (e.g., schwannoma, ependymoma, meningioma) or when two major criteria or one major plus two minor criteria are met (major criteria: unilateral vestibular schwannoma, first-degree relative other than sibling with NF2, ≥2 meningiomas, NF2 pathogenic variant in unaffected tissue—if VAF < 50%, the diagnosis is mosaic NF2; minor criteria: more than one type of tumors, including ependymoma, meningioma, or schwannoma, juvenile subcapsula or cortical cataract, retinal hamartoma, epiretinal membrane in a person < 40 years) [ 74 ]. Genetic analysis uses next-generation sequencing plus multiplex ligation-dependent probe amplification for the detection from 1 exon to multiexon copy number changes and high resolution karyotyping for the identification of chromosomal rearrangements in the NF2 locus with a germline detection rate of 96% in the second generation of families with typical NF2 [ 75 ]. The germline detection rate decreases to 60% in mosaic NF2 [ 76 ].…”
Section: Genetic Tumor Syndromes Correlated With Cranial and Peripher...mentioning
confidence: 99%
“…A genetic testing strategy for SWN is outlined in Figure 2. Paired testing with tumor(s) and saliva/blood is most likely to result in improved diagnostic clarity for individuals with SWN Burns et al (2022) found 13 times greater odds of diagnosis for patients who underwent paired testing with analysis of blood and two or more tumors, compared to patients who underwent germline‐only testing ( p < 0.01) and a six and a half greater odds of diagnosis for patients who underwent paired testing with analysis of blood and one tumor ( p < 0.01) (Burns et al, 2022).…”
Section: Schwannomasmentioning
confidence: 99%